Quote Originally Posted by skeeter View Post
$2\left(-\dfrac{2k}{b^2}+2b\right) = 0 \implies 4\left(-\dfrac{k}{b^2}+b\right) = 0 \implies \color{red}{b = \dfrac{k}{b^2}}$

... this is the value of $b$ that minimizes the volume.


Oh yes of course, thanks.


from the original equation for volume ...

$k = b^2 h \implies \color{red}{h = \dfrac{k}{b^2}}$


take a look again at your first post ... what you were supposed to show?

We must show that h / b = 1, We have now found h and b, we see that h e b are equal, so the outcome is one.